Parfit on Personal Identity: Its Analysis and (Un)importance. (29th February 2016) - Persson, Ingmar
Abstract: This article examines Derek Parfit's claim in Reasons and Persons that personal identity consists in non‐branching psychological continuity with the right kind of cause. It argues that such psychological accounts of our identity fail, but that their main rivals, biological or animalist accounts do not fare better. Instead it proposes an error‐theory to the effect that common sense takes us to be identical to our bodies on the erroneous assumption that our minds belong non‐derivatively to them, whereas they in fact belong to them derivatively in virtue of belonging to some proper parts of them, namely certain features of their brains. However, these features do not meet another necessary condition of being the subject or owner of our minds: the condition of being "accessible" so that we can attribute our mental states to them in everyday life. There is also the problem of specifying these features more precisely. Nothing meets these two conditions, so we are not identical to anything. This conclusion fits well with Parfit's claim that personal identity is not what matters. But although this negative claim is true, it is suggested that Parfit's positive account of what matters is mistaken: it is rather psychological similarity than psychological continuity/connectedness that matters.